PEMANFAATAN ABU DAUN JAGUNG (Zea Mays) SEBAGAI SUMBER SILIKA PADA PEMBUATAN KATALIS Na/ SBA- 15 UNTUK REAKSI TRANSESTERIFIKASI MINYAK JELANTAH - Drajat Bangun Utomo; R R Dirgarini Julia Nurlianti Subagyono; Rahmat GUnawan (JURNAL KIMIA MULAWARMAN, 2018)
Preparation of Na / SBA-15 from corn leaves ash (Zea mays) as a substitute for TEOS (Tetraethyl Orthosilicate) applied as a heterogeneous catalyst in the transesterification reaction of used palm oil and methanol has been performed. The preparation of SBA-15 was conducted by surfactant template method and modification with Na was conducted by impregnation method. SBA-15 from corn leaves ash has a pore size ranging from 4.9 nm to 9.3 nm, a surface area of ​​595 m2/ g, a pore diameter of 3.95 nm and a pore volume of 0.99 cm3/ g. The yeild obtained from the first transesterification process was 96.46% with the free fatty acid content of the product 0.16 mg KOH/ g. The two most prominent methyl ester based on the chromatogram of the transesterification product, the two most prominent methyl ester in the product were methyl palmitate (36,32%) and methyl oleat (36,15%). Keywords : Maize, SBA-15, TEOS (Tetraethyl Orthosilicate), Transesterification of used palm oil